Towards Agile Employee Orientation - Juhala, Veera (My University, 2017)
Words like change, dynamic and unstable are often present when talking about today’s business environment. In response of this hectic atmosphere, the concept of agility is taking over the HRM. Agility can be characterized as an ability to reconfigure resources seamlessly so that an organization can embrace the change instead of just surviving it. Agility can emerge in many areas of HRM but in this paper, orientation is the focus of the research. The purpose of this study is to find out how agility appears in terms of orientation. The theoretical framework of this research is created based on the previous academic research of agility and orientation. The elements of the framework are dynamism, fast organizational learning, workforce scalability and adhocracy. Qualitative case study was selected as the most applicable research method. The research data was collected by conducting 10 semi-structured interviews and also secondary data provided by the company was exploited. The data was analyzed using the agile orientation framework. The results indicated that in the case organization agile orientation appears in the use of multiple orientation tools, cooperation with the academic institutes and exact task-specific orientation. Also, in some parts of the organization, orientation was found customized and beneficial for the newcomer’s possible future positions. The development targets were identified concerning feedback utilization, orientation as a shared responsibility, social assimilation and nurturing wanted behaviors.
Keywords: Agile; Orientation; Newcomer; Socialization; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Henkilöstöjohtamisen maisteriohjelma|en=Master's Programme in Human Resource Managment|